Quantitative Evaluation of the Densities of Ar-N\(_2\) and N\(_2\) Flowing Afterglows at Atmospheric Gas Pressure - André Ricard; Freddy Gaboriau; Anne-Marie Pointu (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Recombination of N- atoms in N2 flowing afterglows is well characterized by optical emission of the N2, positive yellow band at 580 nm which is considered as a signature of N-atoms in the afterglow at reduced and high gas pressures. Production of N2(B,v’) states are analyzed from the N2, positive band intensity in Ar-N2 and N2 afterglows of microwave plasmas and in N2 Corona discharges. In Ar-N2 afterglows of microwave discharges, the N2(B,v’) distribution depends on the N2 fraction in Ar. In pure N2 afterglows, it is found that the N2(B,v’=11) state is enhanced by the N+N atom recombination at pressure up to the atmospheric gas pressure. The other N2(B,v’>0) states are also produced in N2 and Ar-N2 Corona and microwave afterglows by the N+N atom recombination, via the N2(A3\(Σ^+u,w^3Δ u\))attractive curves. It appears that the relaxation of vibrational levels of N2(A) and N2(w) states at the benefit of the N2(B,v’=0) state is enhanced in Corona as in Dielectric Barrier Discharge (DBD) afterglows.